Didactic Principles of Educational Content Based on the Principle of Concentrism in Primary Class Textbooks - Hurriyat, Kurbanova; Dilshoda, Mamatraimova (Researchparks Publishing, 2023)
In the article, the problem of determining the didactic nature of the system of theoretical knowledge in concentrations, how this knowledge has a relationship in the structure of the educational subject, and how to determine the interrelationship between them was formed.lesson